Income shares, secular stagnation, and the long-run distribution of wealth - Luke Petach; Daniele Tavani (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2018)
Four alarming stylized facts have characterized the recent economic history of the United States: (i) a fall in labor productivity; (ii) a fall in the labor share, (iii) an increase in the capital income ratio, and (iv) an increase in the wealth share owned by top income earners. In this paper, we offer a non-Neoclassical explanation for these facts that merges the Pasinetti (1962) approach to differential saving propensities among classes with the theory of induced technical change (ITC) by Kennedy (1964). First, we provide a simple microeconomic rationale for workers' saving propensity being lower than capitalists' based on the empirically-supported argument that consumption peer effects are more prevalent at lower brackets of the income distribution (Petach and Tavani, 2018). We then show that institutional changes that lower the labor share - a decline in unionization, an increase in monopsony power in the labor market, the so-called 'race to the bottom' fostered by a hyper-competitive global environment, or the exhaustion of path-breaking scientific discoveries as argued by Gordon (2015) - can explain the decline in labor productivity growth because of the reduced incentives to innovate to save on labor costs. Combined with ITC, differential savings delivers a direct relationship between the capitalist share of wealth and the capital-income ratio independent of the elasticity of substitution between capital and labor. Finally, we argue that these tendencies are not inevitable: tax policy can be used to implement any wealth distribution, similarly to Zamparelli (2016); while worker-crushing institutional arrangements can be reversed through counteracting policy changes. However, both policy changes appear unlikely given the current institutional and global climate.
Keywords: D31; E24; E25; 330; Capital-Income Ratio; Secular Stagnation; Factor Shares; Wealth Inequality